2015
DOI: 10.5194/tc-9-1579-2015
|View full text |Cite
|
Sign up to set email alerts
|

Century-scale simulations of the response of the West Antarctic Ice Sheet to a warming climate

Abstract: International audienceWe use the BISICLES adaptive mesh ice sheet model to carry out one, two, and three century simulations of the fast-flowing ice streams of the West Antarctic Ice Sheet, deploying sub-kilometer resolution around the grounding line since coarser resolution results in substantial underestimation of the response. Each of the simulations begins with a geometry and velocity close to present-day observations, and evolves according to variation in meteoric ice accumulation rates and oceanic ice sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
226
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(236 citation statements)
references
References 56 publications
9
226
1
Order By: Relevance
“…Under persistent future oceanic forcing, models indicate that thinning will expand to larger areas in the PIG and THG basins, which would contribute to accelerated ice-mass loss and associated sea-level rise [e.g., Joughin et al, 2010Joughin et al, , 2014Cornford et al, 2015]. However, the nonuniform pace of drawdown spreading gives rise to the possibility that the spreading may be decelerated [Joughin et al, 2010] or even cease in certain regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under persistent future oceanic forcing, models indicate that thinning will expand to larger areas in the PIG and THG basins, which would contribute to accelerated ice-mass loss and associated sea-level rise [e.g., Joughin et al, 2010Joughin et al, , 2014Cornford et al, 2015]. However, the nonuniform pace of drawdown spreading gives rise to the possibility that the spreading may be decelerated [Joughin et al, 2010] or even cease in certain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling studies have indicated that rates of ice discharge from this sector are expected to further grow in future, in part due to ongoing ice dynamics and in part due to projected ocean warming [Joughin et al, 2010[Joughin et al, , 2014Favier et al, 2014;Seroussi et al, 2014;Cornford et al, 2015;Goldberg et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…Price et al, 2011;Seroussi et al, 2013;Nowicki et al, 2013;Shannon et al, 2013;Sergienko et al, 2014;Ritz et al, 2015;Cornford et al, 2015). Notably, the basal traction parameterisation -which encapsulates the thermal state, basal roughness, and lithology -is potentially the largest single geophysical uncertainty in projections of the response of ice sheets to climate change (Ritz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Since then several marine ice sheet models of the Antarctic ice sheet have been developed, with varying ways of treating the grounding line, i.e. by increasing locally spatial resolution at the grounding line (Favier et al, 2014;Cornford et al, 2015), by making use of local interpolation strategies at the grounding line (Feldmann et al, 2014;Feldmann and Levermann, 2015;Golledge et al, 2015;Winkelmann et al, 2015) or by parametrizing grounding-line flux based on boundary layer theory (Pollard and DeConto, 2009;Pollard et al, 2015;DeConto and Pollard, 2016).…”
Section: Introductionmentioning
confidence: 99%